2017
DOI: 10.1111/cote.12301
|View full text |Cite
|
Sign up to set email alerts
|

Colour gamuts arising from absorber–dielectric–metal optical resonators

Abstract: Structural coloration is a quickly growing field, encompassing physical and photonic processes such as interference, diffraction, and scattering. In this study, we investigated the optical effects in the visible wavelength range, and in particular, the colour gamuts achievable with absorber–dielectric–metal sandwich structures. These chemical‐free layered structures are highly tunable, easily scaled, optical cavities that are capable of generating remarkable colours whose properties are determined completely b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The calculated colours are obtained from reflectance spectra that include both specular and diffuse components as measured with varying objectives of numerical aperture (NA) = 0.3‐0.75. Samples are listed by descending hue, which correlate with increasing AAO thickness . Photographs correspond to an area of ca .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated colours are obtained from reflectance spectra that include both specular and diffuse components as measured with varying objectives of numerical aperture (NA) = 0.3‐0.75. Samples are listed by descending hue, which correlate with increasing AAO thickness . Photographs correspond to an area of ca .…”
Section: Resultsmentioning
confidence: 99%
“…Anodised aluminium oxide (AAO) is a popular platform for thin film coloration, since a simple electrochemical process creates a dielectric cavity on the surface of the aluminium substrate with a thickness of the order of visible light wavelengths . In a recent work by Oller et al, the authors demonstrated the ability of AAO fabricated using high‐purity aluminium to produce colours in all hues and with high saturation when coated with a metallic absorbing material.…”
Section: Introductionmentioning
confidence: 99%